2021
DOI: 10.5194/hess-2021-554
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Flood forecasting with machine learning models in an operational framework

Abstract: Abstract. Google’s operational flood forecasting system was developed to provide accurate real-time flood warnings to agencies and the public, with a focus on riverine floods in large, gauged rivers. It became operational in 2018 and has since expanded geographically. This forecasting system consists of four subsystems: data validation, stage forecasting, inundation modeling, and alert distribution. Machine learning is used for two of the subsystems. Stage forecasting is modeled with the Long Short-Term Memory… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Machine learning methods provide great versatility (Shen, 2018;Shen et al, 2018;Reichstein et al, 2019) and have demonstrated unprecedented accuracy in various modelling tasks like predictions in un-gauged basins (PUB, e.g. Kratzert et al, 2019b;Prieto et al, 2019), in transfer learning to data-scarce regions (Ma et al, 2021) or flood forecasting (Frame et al, 2021;Nevo et al, 2021).…”
Section: Machine Learning In Hydrologymentioning
confidence: 99%
“…Machine learning methods provide great versatility (Shen, 2018;Shen et al, 2018;Reichstein et al, 2019) and have demonstrated unprecedented accuracy in various modelling tasks like predictions in un-gauged basins (PUB, e.g. Kratzert et al, 2019b;Prieto et al, 2019), in transfer learning to data-scarce regions (Ma et al, 2021) or flood forecasting (Frame et al, 2021;Nevo et al, 2021).…”
Section: Machine Learning In Hydrologymentioning
confidence: 99%
“…The East Asian areas border the North Pacific to progressively hit by a greater number of disastrous flood catastrophes as a direct result of the bigger and more powerful storms. ANNs models be effective and quickly forecasting river system floods in limited locations (Nevo et al, 2019;Salas et al, 2018). In Japan, typhoon-& heavy-rainfall-prone areas have seen river system disasters in the last 3-4 years (Realestate Blog, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It estimated that for each dollar spent on such systems, nine dollars of damages are prevented [3]. Machine learning is well suited to help provide reliable operational flood forecasts at large scales [4].…”
Section: Introductionmentioning
confidence: 99%